A szegedi Polgári Iskolai Tanárképző Főiskola és a Ferenc József Tudományegyetem együttműködése a tanárképzés szolgálatában (1928–1947) - Fizel, Natasa (Gerundium, 2019)
The Cooperative Framework between the National Civic School Teacher Training College and the Ferenc József University in the Service of Teacher Training (1928–1947). In my study I demonstrate the creative process of the cooperative framework between two institutions of high education in Szeged, the National Civic School Teacher Training College and the Ferenc József University from the very first school year in Szeged in 1928 until the last one in 1947, that is, until a dispute that ended their cooperation. The discussion was aimed at the rate of role of the two institutions in civic school teacher training. My goal is to review the historical background and the method of research and then give answers to the following questions: what stages did the coming about of the cooperation go through? What effect did this collaboration have on the everyday life of the students? How is the dispute about the creation of the framework presented in the most important organ of civic school teachers, Polgári Iskolai Tanáregyesületi Közlöny (Civic School Teachers Association Gazette)?